BIAYA CSR: VOLUNTARY DISCLOSURE, INVESTASI DAN SINYAL? - ST. Dwiarso Utomo; Vonny Meilinasari; Zaky Machmuddah (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
The main issue of the research is concerning CSR expenditure related with voluntary disclosure, investment (ROA) and signaling (divident). Efectivity of social cost dilemma is the trigger of economic motive or social motive in CSR expenditure. The purpose of the current research is to examine the effect of CSR expenditure to voluntary disclosure, CSR expenditure to investment (ROA) and CSR expenditure to signaling (divident). Population of the research was all companies listed in Indonesian Stock Exchange, from 2013-2014. The total of research samples were 141 companies with 69 annual reports done by using purposive sampling method. Data analysis used was classical assumption test and hypothesis test with multiple regression analysis. The result of the research indicated that CSR expenditure positively and significantly affected to investment (ROA). Meanwhile, CSR expenditure did not significantly affect to voluntary disclosure and signaling (divident). The practical implication of the research is that the firm should be based on community excess concept in social responsibility practice. Keywords: CSR expenditure, voluntary disclosure, investment and signaling.